From Research to Market A Comprehensive Guide - Ossa, Alvaro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
Unlock the secrets to transforming research into impactful products and services that reach the market. This book is a vital resource for anyone involved in the journey from academia to commercialization. It outlines the main stages and key milestones of technology transfer in a clear and engaging manner, featuring real-world examples of successful university research outcomes. Analyse the circumstances behind their success and learn the essential steps for a successful technology transfer process. Designed as a go-to reference for researchers, doctoral and master's students, scientific entrepreneurs, and academics focused on innovation and entrepreneurship, this book is also invaluable for technology managers at universities, research centres, and public agencies. Enhance your understanding of technology transfer and gain practical knowledge to navigate this complex field successfully.
Commercialization of science and technology -- Commercial validation -- Intellectual property -- Technology commercialization -- Science-based entrepreneurship -- Financing -- Technology transfer management -- Technology transfer offices.
Keywords: Medicine -- Research; Biology -- Research; Biotechnology; Biomedical engineering; Entrepreneurship; New business enterprises; Food science; Biomedical Research; Biotechnology; Biomedical Engineering and Bioengineering; Entrepreneurship; Biomedical Devices and Instrumentation; Food Science